THE APPLICATION OF THE NET PROMOTER SCORE (NPS) METHOD IN MEASURING CUSTOMER SATISFACTION IN THE RETAIL INDUSTRY IN MEDAN - Khairunnida; Renny Lubis; Rizaldy Khair (Jurnal Ekonomi, 2023)
The retail industry in Medan City is one of the most competitive industries. Tight business competition in the retail industry requires companies to constantly improve the quality of their products and services. Therefore, measuring customer satisfaction is very important for companies to find out the extent to which the quality of their products and services meets customer needs and expectations. Research Methods Net Promoter Score (NPS) is one of the popular methods used to measure customer satisfaction. This method allows companies to measure customer satisfaction using one simple question, namely "Would you recommend our products or services to others?" with an answer scale from 0 to 10. The NPS method has been used by many companies around the world to increase customer satisfaction and improve the quality of their products and services. However, there are still few retail companies in Medan City that use the NPS method to measure customer satisfaction. The urgency of the research is to find out the quality of their products and services to meet customer needs and expectations, the use of NPS as a tool to measure customer satisfaction and provide recommendations to retail companies to improve the quality of products and services. Research objectives to apply the Net Promoter Score method in measuring customer satisfaction in the retail industry in Medan City. This research also aims to find out what factors affect customer satisfaction and provide recommendations to retail companies to improve the quality of their products and services. In this study, a quantitative approach with survey method is used to collect data from respondents through questionnaires distributed online or directly to customers of several retail companies in Medan City.